Pengaruh Lama Perendaman Daging Ayam Petelur Afkir Bagian Paha dalam Blend Kunyit (Curcuma domestica) dan Jahe (Zingiber officinale) terhadap Kualitas Fisik - Lukman Prayogo; Agustinus Hantoro Djoko Rahardjo; Elly Tugiyanti (Fakultas Peternakan Universitas Jenderal Soedirman, 2020)
Background. The study aimed to determine about the effect of soaking time of culled chicken laying meat thighs in blend turmeric (Curcuma domestica) and ginger (Zingiber officinale) on physical quality Materials and methods. with material used is meat thighs as much as 20 out of 20 thighs laying age 80 weeks, 4 liters of aqueous, 600 grams of turmeric, 600 grams of ginger, and 75 ml of buffer solution. The research was conducted by experimental method using a completely random design with 4 treatments and 5 replays. The advanced test used is advanced polynomial orthogonal testing. Treatment consists of (P0) = soaking for 0 minutes, (P1) = soaking for 10 minutes + 30% blend of turmeric and ginger, (P2) = soaking for 20 minutes + 30% blend of turmeric and ginger, and (P3) = soaking for 30 minutes + 30% blend turmeric and ginger. The variables measured are tenderness, pH, water holding capacity, and cooking losses. The data obtained is analyzed with analysis of variance (ANOVA). Results. The results of analysis of variance showed that the length of soaking with the blend of turmeric and ginger had a significantly effect (P<0.05) on tenderness and cooking losses but had no significant effect (P>0.05) on pH and water holding capacity. Conclusion. The results of the study can be concluded that soaking of chicken meat laying the thighs in a blend of turmeric and ginger with a blend concentration of 30% for 30 minutes is most optimal in increasing the value of tenderness and decreasing the cooking losses, but the pH value and water holding capacity of meat is the same.